Editorial Introduction - Suzanne Porath (Networks: An Online Journal for Teacher Research, 2015)
Too often teacher research is conducted in isolation, but deeper reflection and action can occur when teacher research is conducted and/or shared with others. In Volume 17, Number 2 of Networks: An Online Journal for Teacher Research educators/researchers illustrate how collaboration with others enhanced their understanding of their own practice. This issue provides a broad range of perspectives in using teacher research including teacher candidates, classroom teachers, and graduate students.